PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN - Indah Surti; Fitria Nur Anggraeni (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
The purpose of this study was to determine the effect of service quality on customer satisfaction. The research method used is quantitative with descriptive. The population in this study were consumers of Waroeng Steak Cafe & Resto in South Jakarta with a sample of 91 and the sampling technique used was Accidental Sampling. Furthermore, the analysis method uses simple linear regression consisting of descriptive analysis of the questionnaire, validity test, reliability test, correlation coefficient test, determination coefficient test and hypothesis test. The results showed that service contributed significantly to satisfaction. This happens, caused by emotional interaction. Therefore, it is important to strengthen the characteristics of employees in service. Furthermore, services should be used as a spearhead in influencing consumers. This will affect the long term and wide area